Pendidikan Ekonomi Syariah di Pesantren Nurul Huda Bendungan Kraton Pasuruan dan Dampaknya terhadap Pemberdayaan Ekonomi Santri - Moh. Irham Maulana (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Abstract Purpose – This study aims to analyze the model of Islamic economic education implemented at Pesantren Nurul Huda Bendungan, Kraton, Pasuruan, and to explore its implications for students’ economic empowerment within the broader framework of Islamic education.;. Design/methodology/approach - This research employed a qualitative case study approach. Data were collected through in-depth interviews, observation, and documentation involving pesantren leaders, teachers, students, and managers of business units. Data were analyzed using an interactive model of data reduction, data display, and conclusion drawing. Research limitations/implications – This study is limited to a single pesantren context, which may restrict broader generalization. However, the findings provide practical and theoretical implications for developing Islamic economic education models that integrate classical Islamic principles with community-based economic empowerment strategies. Findings – The study reveals that Islamic economic education in the pesantren is implemented through an integrative model combining normative fiqh muamalah learning, value internalization, and structured cooperative-based business practices. These practices function as practical learning spaces that foster students’ economic awareness, work ethics, and independence. Originality/value – This study contributes to Islamic education literature by positioning pesantren not merely as economic institutions but as pedagogical spaces that systematically integrate classical fiqh principles with structured economic empowerment practices.